Sundanese Culture Local Wisdom Based Leadership: The Dynamics of Government Leadership of Purwakarta Regent Period 2008-2018 - Ednawan Prihana; Ngadisah; Muhadam Labolo; Kusworo (GoAcademica Research & Publishing, 2020)
This study aims to analyze the dynamics of local government leadership based on the wisdom of Sundanese culture in Purwakarta Regency in the period 2008-2018. This study uses a qualitative research design, research data collection techniques using documentation studies, interviews and observations. The results of this study found that the leadership of the Purwakarta Regent in the period 2008-2018 based on Sundanese culture local wisdom with the concept of Sunda Dasa Prasanta's leadership could be accepted and supported by the majority of the people of Purwakarta Regency. In his leadership, there are dynamics that cause polemics and pros and cons in the community, but the dynamics that arise can be resolved properly by communicating and holding communication forums. The